Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/cells8080901
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish in Inflammasome Research

Abstract: Inflammasomes are cytosolic multiprotein complexes that regulate inflammatory responses to danger stimuli and infection, and their dysregulation is associated with an increasing number of autoinflammatory diseases. In recent years, zebrafish models of human pathologies to study inflammasome function in vivo have started to emerge. Here, we discuss inflammasome research in zebrafish in light of current knowledge about mammalian inflammasomes. We summarize the evolutionary conservation of inflammasome components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 91 publications
0
28
0
Order By: Relevance
“…Pyroptotic cell death is associated with the activity of inflammatory caspases, like Caspase 1 and Caspase 4/5/11, and is characterized by the formation of Gasdermin pores in the cell membrane [36][37][38] . We have recently found that Caspase a (Caspa) is the Caspase-family member that induces pyroptosis of Mm-infected macrophages in zebrafish via Gasdermin Eb (Gsdmeb) 39,40 . Thus, we analyzed Caspa activity at 2dpf, the time point where we observed increased cell death in dram1 Δ19n/Δ19n .…”
Section: Dram1 Deficiency Results In Increased Pyroptotic Cell Death mentioning
confidence: 99%
“…Pyroptotic cell death is associated with the activity of inflammatory caspases, like Caspase 1 and Caspase 4/5/11, and is characterized by the formation of Gasdermin pores in the cell membrane [36][37][38] . We have recently found that Caspase a (Caspa) is the Caspase-family member that induces pyroptosis of Mm-infected macrophages in zebrafish via Gasdermin Eb (Gsdmeb) 39,40 . Thus, we analyzed Caspa activity at 2dpf, the time point where we observed increased cell death in dram1 Δ19n/Δ19n .…”
Section: Dram1 Deficiency Results In Increased Pyroptotic Cell Death mentioning
confidence: 99%
“…The large p20 and small p10 domains of the 35 putative C. gigas caspases identified by a BLAST search, together with the 23 previously identified caspases in bivalves, were aligned with caspases homologues (caspase-1 -caspase-10) of vertebrates and other invertebrate species using the default parameter of MUSCLE v3.8.31 [85] and edited manually in case of errors. Representatives of caspase homologues to vertebrate caspase-11caspase-16 or tunicates caspase-17caspase-22 were excluded as previous research has shown that these caspases are specific to these subphyla [86,87]. For those putative caspases, which did not contain a small p10 domain, remaining protein sequence downstream to the large p20 domain were used in the alignment instead.…”
Section: Identification Bivalve Caspases and Phylogenetic Analysismentioning
confidence: 99%
“…The large p20 and small p10 domains of the 35 putative C. gigas caspases identi ed by a BLAST search, together with the 23 previously identi ed caspases in bivalves, were aligned with caspases homologs (caspase-1 -caspase-10) of vertebrates and other invertebrate species using the default parameter of MUSCLE v3.8.31 (101) and edited manually in case of errors. Representatives of caspase homologs to vertebrate caspase-11 -caspase-16 or tunicates caspase-17 -caspase-22 were excluded as previous research has shown that these caspases are speci c to these subphyla (102,103). For those putative caspases, which did not contain a small p10 domain, remaining protein sequence downstream to the large p20 domain were used in the alignment instead.…”
Section: Methodsmentioning
confidence: 99%